(untitled) (Research, Society and Development, 2020)
Coastal Zone is an area where ocean, land, and environment interact with one another; therefore, it is lively and varied in nature. The coastal zones in Bangladesh is being frequently attacked by cyclones, storm surge, sea level rise, which have affected terribly this low lying coastal zone. The multifaceted coastal zone prerequisites all-inclusive integrated approaches to manage. This study aims to identify the background of the socio-economic problems of the people of coastal zone particularly in the eastern belt. It also discusses the various problems along the coastal areas, and the rationality of coastal governance and management for sustainable development, framework for solving the coastal issues in the eastern zone, climate change and environmental impacts, and policy recommendations for coastal development and management so as to adapt climate change vulnerability (Ahmad, 2019). However, no socio-economic development policy has been taken so far for the coastal people who are the extreme victims of the climate change, natural calamities, typhoons and torpedoes. This study has been done on the basis of both primary and secondary sources of data. The authors of this research have exchanged views with the people living in the eastern coastal belt of Bangladesh to know about the socio-economic condition.